Four‐year follow‐up of weight loss maintenance using electronic medical record data: The PROPEL trial - Peter T. Katzmarzyk; Emily F. Mire; Ronald Horswell; San T. Chu; Dachuan Zhang; Corby K. Martin; Robert L. Newton; John W. Apolzan; Eboni G. Price‐Haywood; Dan Fort; Thomas W. Carton; Kara D. Denstel; et al. (Obesity Science & Practice)
Abstract Rationale Short‐term weight loss is possible in a variety of settings. However, long‐term, free‐living weight loss maintenance following structured weight loss interventions remains elusive. Objective The purpose was to study body weight trajectories over 2 years of intensive lifestyle intervention (ILI) and up to 4 years of follow‐up versus usual care (UC). Methods Data were obtained from electronic medical records (EMRs) from participating clinics. Baseline (Day 0) was established as the EMR data point closest but prior to the baseline date of the trial. The sample included 111 ILI and 196 UC patients. The primary statistical analysis focused on differentiating weight loss trajectories between ILI and UC. Results The ILI group experienced significantly greater weight loss compared with the UC group from Day 100 to Day 700, beyond which there were no significant differences. Intensive lifestyle intervention patients who maintained ≥5% and ≥10% weight loss at 24 months demonstrated significantly greater weight loss (p < 0.001) across the active intervention and follow‐up. Conclusions Following 24 months of active intervention, patients with ILI regained weight toward their baseline to the point where ILI versus UC differences were no longer statistically or clinically significant. However, patients in the ILI who experienced ≥5% or ≥10% weight loss at the cessation of the active intervention maintained greater weight loss at the end of the follow‐up phase. Clinical Trial Registration ClinicalTrials.gov: NCT02561221.